Performance and egg quality of laying Japanese quails (Coturnix coturnix japonica) reared in hot climate as a function of digestible arginine: lysine ratios in the diet - MORAIS, MARCOS VINÍCIUS MARTINS; LIMA, HEDER JOSÉ D’AVILA; SILVA, FERNANDA NUNES ALBERNAZ; GOMES, MARCUS VINICIUS FIGUEIREDO CAMPOS (The Indian Journal of Animal Sciences, 2022)
The objective of this study was to determine the ideal digestible arginine: lysine ratio in the diet of laying Japanese quails reared in hot climate, on the variables of productive performance and egg quality. Completely randomized experimental design was adopted with five diets and six replications containing eight laying quails (Coturnix japonica) per experimental unit, totaling 240 birds with an average weight of 169.6±0.005 g and 40 weeks of age with an initial egg production of 79.18±3.32%. The digestible arginine: lysine ratios were 110%, 120%, 130%, 140% and 150%. The arginine: lysine ratios analyzed were not able to influence feed intake, egg production, commercial eggs, egg weight, egg mass, feed conversion per egg mass (FCEM) and per dozen eggs (FCDZ); however, there was a quadratic effect for the variation in body weight. There was no significant difference for egg quality characteristics. The 110% digestible arginine: lysine ratio in the diet of laying Japanese quails reared in a hot climate is sufficient to maintain the productive performance and the egg quality.